Pandemian ja digitalisaation vaikutukset käräjäoikeuksien toimintaan - Ervo, Laura; Autio, Anna-Liisa (Lakimies, 2025)
The Covid pandemic and digitalisation: Effects in the lower courts It was a stroke of luck for Finland that the latest reform for streamlining court proceedings entered into force precisely in 2019. This reform introduced digital solutions for participation and for the normal daily workflow in Finnish district courts. Both the Code of Judicial Procedure and Criminal Procedure Act were amended. After the 2019 reform, well in advance of the onset of the Covid pandemic, the possibility of holding remote or hybrid hearings was already in regular use under normal conditions. It could be said that it was a blessing in disguise that the reform was in force already a year before the real need for it became apparent. It has been much easier to tackle the effects of the pandemic than it would have been had the reform not been in effect. Many practical and legal problems still exist. It can even be said that due process and the principle of legality can be in danger. The new situation, in conjunction with previous reforms, has introduced changes in the basic principles of court proceedings. This is also a matter of how the courts interact with their customers.